4b-6+2r=-48

Simple and best practice solution for 4b-6+2r=-48 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4b-6+2r=-48 equation:


Simplifying
4b + -6 + 2r = -48

Reorder the terms:
-6 + 4b + 2r = -48

Solving
-6 + 4b + 2r = -48

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 4b + 6 + 2r = -48 + 6

Reorder the terms:
-6 + 6 + 4b + 2r = -48 + 6

Combine like terms: -6 + 6 = 0
0 + 4b + 2r = -48 + 6
4b + 2r = -48 + 6

Combine like terms: -48 + 6 = -42
4b + 2r = -42

Add '-2r' to each side of the equation.
4b + 2r + -2r = -42 + -2r

Combine like terms: 2r + -2r = 0
4b + 0 = -42 + -2r
4b = -42 + -2r

Divide each side by '4'.
b = -10.5 + -0.5r

Simplifying
b = -10.5 + -0.5r

See similar equations:

| 3x+12=5x+42 | | a+2s=3(s-2)+1 | | x^2+17x-193=0 | | t=x^2+3x | | 2a^2+23a+45=0 | | 8(-38x+32)=-43(-21+8x) | | 10(x+1)-4v=3(2v+3)-11 | | 3n-4=2n | | 1.1x-1.62=-1.4 | | 3x+7=7-(4x-9) | | 5.75+5-k= | | x=t^2+3t | | 800x=100x^2 | | 2(5x+3)=98+3x | | 9(8z+9)+6=-273 | | -6(x-7)-7=-7x+2 | | -2.5--0.7=x | | 1.1x=3y-0.4 | | 3p+3.7=9.1 | | -13=x+72 | | n-5=-13 | | .2(x+3)-.5(x+3)=-0.3-0.9 | | 496=62x | | 3/8c=6 | | (n-7)-2n=12 | | 10-2(x+10)=60 | | 7x-1=23+7x | | x+4.07=6.46 | | 6x+6=11-2x | | 8x-15=155 | | -b+8=-15 | | 7s=-49 |

Equations solver categories